2015
DOI: 10.18632/oncotarget.5717
|View full text |Cite
|
Sign up to set email alerts
|

The role of Rak in the regulation of stability and function of BRCA1

Abstract: BRCA1 is an important player in the DNA damage response signaling, and its deficiency results in genomic instability. A complete loss or significantly reduced BRCA1 protein expression is often found in sporadic breast cancer cases despite the absence of genetic or epigenetic aberrations, suggesting the existence of other regulatory mechanisms controlling BRCA1 protein expression. Herein, we demonstrate that Fyn-related kinase (Frk)/Rak plays an important role in maintaining genomic stability, possibly in part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…More recently, breast cancer susceptibility gene 1 (BRCA1) was identified as a bona fide FRK substrate [41]. The effect of BRCA1 phosphorylation by FRK is reminiscent of the regulation of PTEN stability by FRK, described earlier.…”
Section: Substrates/binding Partnersmentioning
confidence: 90%
See 3 more Smart Citations
“…More recently, breast cancer susceptibility gene 1 (BRCA1) was identified as a bona fide FRK substrate [41]. The effect of BRCA1 phosphorylation by FRK is reminiscent of the regulation of PTEN stability by FRK, described earlier.…”
Section: Substrates/binding Partnersmentioning
confidence: 90%
“…Another study reported elevated FRK mRNA levels in two out of six breast tumour tissue samples analysed. A very recent study revealed FRK expression to positively correlate with BRCA1 expression in tissue samples corresponding to invasive ductal breast carcinoma cases, as determined via IHC analyses [41]. Further, the study reported FRK as an under-expressed protein in nearly 20 % cases examined (14 out of 70 cases) [41].…”
Section: Cancer Cell Lines and Tissuesmentioning
confidence: 97%
See 2 more Smart Citations
“…In HepG2, we observed a partial LOH for the 5' portion FRK (Table S3). Since its discovery in 1993, FRK was first attributed as a tumor suppressor (Craven et al 1995;Oberg-Welsh et al 1998;Brauer and Tyner 2009;Kim et al 2015); however, further investigations show that FRK appears to play a tissue-specific oncogenic role in liver, pancreatic, breast and brain cancers and has been proposed as a therapeutic target (Goel and Lukong 2016). Interestingly, it was shown ectopic overexpression of FRK in HepG2 had no effect on cell proliferation, while this overexpression results in a significant growth reduction (p-value < 0.05) was observed in HepG2 cells with FRK-knockdown .…”
Section: Discussionmentioning
confidence: 99%